KONVERSI AGAMA DAN FORMASI IDENTITAS: Tionghoa Muslim Kudus Pasca-Indonesia Orde Baru - Amaruli, Rabith Jihan; Utama, Mahendra Pudji (Faculty of Humanities, Diponegoro University, 2015)
This paper discusses about religion conversion and assimilation dillema in Kudus Chinese Moslem. As a reality there is no guarantee that the assimilation will be finish with the conversion of Chinese to the Islam. Hopefully, the understanding about plurality (kebhinekaan) will be a strong fundament in the cultural integration. This study found that the Chinese choose Islam, especially in post-New Order, caused by two main motivations coming from itself and environment. The relationship of post-conversion of Chinese muslim, made at a crossroad. On the one hand, the Chinese muslim still considered strange to some native communities. The still come under suspicion only purely politically and economically, while on the other hand their proximity to the government and the muslim community make them â€œshunnedâ€by the Chinese people.